Nanoplasmonic Sensors - Dmitriev, Alexandre (Integrated Analytical Systems, 2012)
This book is a compendium of the finest research in nanoplasmonic sensing done around the world in the last decade. It describes basic theoretical considerations of nanoplasmons in the dielectric environment, gives examples of the multitude of applications of nanoplasmonics in biomedical and chemical sensing, and provides an overview of future trends in optical and non-optical nanoplasmonic sensing. Specifically, readers are guided through both the fundamentals and the latest research in the two major fields nanoplasmonic sensing is applied to - bio- and chemo-sensing - then given the state-of-the-art recipes used in nanoplasmonic sensing research.